A Review on Epidemiology, Clinical Manifestation and Diagnostic Approach of Dengue in Bangladesh Perspective - Naznin, Sidratul Muntaha; Hossain, Md Mostafa; Iftekhar, Quazi Sazzad; Ahasan, Tarikul (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Dengue is an arboviral disease caused by dengue virus; single positive stranded RNA virus of the family Flaviviridae. Symptomatic dengue infection causes a wide range of clinical manifestations; from mild dengue fever (DF) to potentially fatal disease, such as dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS). Dengue is endemic in Bangladesh with recurrent outbreak and is one of the major public health concerns in current period. Therefore; we conducted a literature review to analyze demography, epidemiology, pathogenesis, clinical feature and diagnosis of dengue virus infection. Methods: According to the PRISMA guidelines, the references were selected from PubMed, Web of Science and Google Scholar database using search strings containing a combination of terms that included ”dengue”, “Bangladesh”, “epidemiology”, “outbreak”,” pathogenesis”, “clinical manifestation”, “demography “and “diagnosis”. Quality of references was evaluated by independent contributors. Results: About 167,700 confirmed dengue cases were reported at 16’september’2023 in Bangladesh. Although dengue is endemic in Bangladesh, the current dengue surge is unusual in terms of seasonality and the early sharp increase in comparison to previous years, where the surge started around –late June. Plasma leakages are the main pathophysiological hallmark that distinguishes DHF from DF. Severe plasma leakage can result in hypovolemic shock. Various factors are thought to impact disease presentation and severity. Virus segregation in cell cultures, nucleic acid demonstration by polymerase chain reaction (PCR), and serological detection of viral antigens (such as NS1) or particular antibodies are the preferred microbiological assays for dengue detection. Currently, no specific drugs and licensed vaccines are available to treat dengue disease in any of its clinical presentations for all age group. Conclusion: Understanding the clinical manifestation of dengue infection, prompt diagnosis, appropriate treatment, active and continuous surveillance of cases and vectors are the essential determinants for dengue prevention, control and reducing fatality rate. J Bangladesh Coll Phys Surg 2023; 41: 69-81